Heterogeneity of vascular endothelial cells with relevance to diagnosis of vascular tumours. - Kuzu, I. (1992)
AIMS: To determine the distribution of factor VIII related antigen, CD31, CD34 and CD36 in normal and malignant human vascular tissues using a panel of well characterised monoclonal antibodies. METHODS: Frozen and fixed material from a wide range of normal tissues and routinely processed material from 43 benign and malignant vascular tumours were examined. Single immunocytochemical labelling was performed using the APAAP technique. Double staining involved the sequential use of APAAP with the peroxidase method. RESULTS: Human vascular endothelium was antigenically heterogeneous. One of the most restricted markers was factor VIII related antigen, despite its having been widely used in diagnostic pathology as a marker of vascular endothelium and of the tumours which arise from it. Three antibodies against factor VIII related antigen, CD31 (JC70) and CD34 (QBend 10) were identified as immunostaining routinely processed, formalin fixed, paraffin wax sections. Each antibody gave different staining when tested on a range of vascular tumours, both benign and malignant. CONCLUSIONS: A small panel of three reagents (factor VIII related antigen, CD31 (JC70) and CD34 (QBend 10)) should be used by diagnostic pathologists who want to show the presence of cells of endothelial origin in routine material.